From Internalization to Social Norms: An Integrative Model of Religious Moderation in Rural Indonesia - Bambang Samsul Arifin; Uus Ruswandi; Badrudin Badrudin; Ratu Utami; Yuli Marlina (SCAD Independent, 2026)
Religious moderation is critical to fostering social cohesion in rural Indonesian communities, where differences in beliefs and practices can occasionally cause conflict. This study develops and evaluates a model for internalizing religious moderation that incorporates four critical societal elements: family, school, community, and government. The approach supports the fundamental ideals of justice, tolerance, patriotism, and reconciliation. To investigate how these values are nurtured in rural settings, data were collected using a qualitative case study technique, including observations, in-depth interviews, and document analysis. The findings indicate that religious moderation is internalized in three stages: value transformation, in which individuals are introduced to moderation principles; value transaction, in which these principles are practiced and exchanged within social environments; and value trans-internalization, in which moderation becomes a deeply ingrained part of communal life. Furthermore, three essential approaches (understanding, habituation, and role modelling) help establish these values and promote a culture of moderation. By supporting these ideas, societies experience fewer religious conflicts and increased social cohesion, resulting in long-term stability and harmony.